Effects of increased stocking density and heat stress on growth, performance, carcase characteristics and skeletal properties in turkeys. (3rd January 2015) - Jankowski, J.; Mikulski, D.; Tatara, M. R.; Krupski, W.
Abstract : Effects of increased stocking density and heat stress on growth, feed conversion, carcase characteristics and skeletal system properties in turkeys were determined. One‐day‐old males (n=1674) were divided into two weight‐matched groups exposed to different environmental conditions. Controls were reared at a stocking density of 2.8 birds/m 2 and at thermo‐neutral temperature (TnT group), while the experimental group was exposed to heat‐stress (HSID group) and reared at a stocking density of 3.4 birds/m 2 and ambient temperature increased by 5°C. At 28 days of age, 27 birds from each group were sacrificed, while at 126 days of age, 54 birds from each group were slaughtered. Increased stocking density and ambient temperature during the first four weeks of life increased the body weight (BW) of turkeys and weight, length, volume, vertical internal and horizontal external diameters of the tibia in the HSID group compared with the TnT group (P<0.05). In turkeys older than four weeks, increased stocking density and ambient temperature significantly decreased daily feed intake, final BW and relative weight of drumstick muscle by 4.7 per cent, 4.0 per cent and 3.3 per cent, respectively (P<0.05). The weight, length, volume, vertical and horizontal diameters, cross‐sectional area, second moment of inertia, volumetric bone mineral density, maximum elastic strength and ultimate strength of bones were significantly lower in turkeys in the HSID group (P<0.05) at 126 days compared with turkeys in the TnT group at the same age. These results indicate that, up to four weeks of age, turkeys tolerate increased stocking density and heat stress better than birds between 5 and 18 weeks of age.